Cytogenetic study of some Hordeum L. species in Iran - Sheidai, Masoud; Rashid, Samaneh (Acta Biologica Szegediensis, 2007)
Karyotypic and meiotic studies were performed in 17 populations of seven Hordeum species and subspecies showing the occurrence of 2n = 2x = 14, 2n = 4x = 28 and 2n = 6x = 42. Tetraploid level for H. distichon and hexaploid level for H. leporinum are new reports. The chromosomes were mostly metacentric and sub-metacentric. Significant differences in the size of chromosomes and their arm ratios indicated the occurrence of quantitative changes in the chromatin (DNA) material during species diversification. The species also differed in their karyotypic formulae possibly due to the occurrence of chromosome structural changes. Comparison of the total haploid chromatin length among populations of H. bulbosum and H. glaucum having diploid and tetraploid chromosome numbers, indicated that the occurrence of polyploidy is not associated with a significant increase in the amount of DNA and almost the same DNA content has been distributed among the chromosomes of the tetraploid population. The relative karyotypic data were used for multivariate analysis, which showed karyotypic variations among Hordeum species and populations studied.